Factors Affecting Credit Service Demand of Pak Phli Agricuitural Co-operatives Ltd. Members, Nakhonnayok Province - พานกระดึง, วิไลพร (Journal of Humanities and Social Sciences, Rajapruk University, 2018)
This research aims to: 1) to identify the level of demand for credit services of the members from Pak Phli Agricuitural Co-operatives Ltd. 2) to study the expectations of its members in providing credit Pak Phli Agricuitural Co - operatives Ltd. Members 3) to identify characterized the relationship between general economic conditions and the members of the cooperative needs to take a loan of Pak Phli Agricuitural Co-operatives Ltd. members 4) the relationship between baseline characteristics and economic condition of the cooperative members with the expectation of using credit Pak Phli Agricuitural Co-operatives Ltd. members. The population of the research included 268 members of Pak Phli Agricuitural Co-operatives Ltd. Collect data from questionnaires and were interviewed by the committee. The statistics used for data analysis were percentage, mean, standard deviation, chi-square test. The research found that 1) the level of demand for credit services of Pak Phli Agricuitural Co-operatives Ltd. Members is at the high level. 2) the expectations of its members in providing credit Pak Phli Agricuitural Co-operatives Ltd. Members are at the high level, 3) the relationship between basic characteristics and economic condition of Pak Phli Agricuitural Co-operatives Ltd. Members, it was found that aging is associated with. demand for loan services of Pak Phli. 4) the relationship between basic characteristics and economic condition of Pak Phli Agricuitural Co - operatives Ltd. Members, the study was found that the age of the member's monthly income, and there is correlation between the expenditure of households, most expenditure In relation to the expectations of the loan Pak Phli Agricuitural Co-operatives Ltd. members.